SPECIFICITIES OF BRAND DESIGN IN HIGHER EDUCATION - Ilieva, Silvina; Ozanian, Kristin (Innovation in Woodworking Industry and Engineering design, 2024)
The report focuses on the problems and specificities of brand design of higher education institutions in Bulgaria, including an analysis of Medical University – Plovdiv and Technical University – Sofia, Plovdiv branch. The paper discusses the creation of a graphic identity, the development of a brandbook and its implementation. In addition, the benefits of brand design in higher education and its application in all aspects are presented. The report also includes a comparison with practices in world-renowned universities. The main objective is to explore how brand design can improve the communication, attractiveness and reputation of higher education institutions.